Interplanetary Rotation of 2021 December 4 Coronal Mass Ejection on Its Journey to Mars - Mengxuan Ma; Liping Yang; Fang Shen; Chenglong Shen; Yutian Chi; Yuming Wang; Yufen Zhou; Man Zhang; Daniel Heyner; Uli Auster; Ingo Richter; Beatriz Sanchez-Cano (The Astrophysical Journal)
The magnetic orientation of coronal mass ejections (CMEs) is of great importance to understand their space weather effects. Although plenty of evidence suggests that CMEs can undergo significant rotation during the early phases of evolution in the solar corona, there are few reports that CMEs rotate in the interplanetary space. In this work, we use multispacecraft observations and a numerical simulation starting from the lower corona close to the solar surface to understand the CME event on 2021 December 4, with an emphatic investigation of its rotation. This event is observed as a partial halo CME from the back side of the Sun by coronagraphs and reaches the BepiColombo spacecraft and the Mars Atmosphere and Volatile EvolutioN/Tianwen-1 as a magnetic flux-rope-like structure. The simulation discloses that in the solar corona the CME is approximately a translational motion, while the interplanetary propagation process evidences a gradual change of axis orientation of the CME’s flux-rope-like structure. It is also found that the downside and the right flank of the CME moves with the fast solar wind, and the upside does in the slow-speed stream. The different parts of the CME with different speeds generate the nonidentical displacements of its magnetic structure, resulting in the rotation of the CME in the interplanetary space. Furthermore, at the right flank of the CME exists a corotating interaction region, which makes the orientation of the CME alter and also deviates from its route due to the CME. These results provide new insight into interpreting CMEs’ dynamics and structures during their traveling through the heliosphere.